Effect of the Partial Substitution of Sodium Chloride on the Gel Properties and Flavor Quality of Unwashed Fish Mince Gels from Grass Carp - Ruobing Pi; Gaojing Li; Shuai Zhuang; Qinye Yu; Yongkang Luo; Yuqing Tan; Ruitong Dai; Hui Hong (Foods, 2022)
Excessive salt is usually required to maintain good gel properties and quality characteristics for unwashed fish mince gels (UFMG). This study aimed to investigate the effects of partial sodium chloride substitution (30%) with different substitutes (potassium chloride, disodium inosine-5′-monophosphate, basil) on the gel and flavor properties of UFMG from Ctenopharyngodon idellus. The results indicated that the texture and gel strength of NK (30% NaCl was replaced with 30% KCl) were fairly similar to that of N group (NaCl only), and the whiteness had improved significantly (p < 0.05), while the product eventually yielded a certain bitter taste. The addition of disodium inosine-5′-monophosphate (DIMP) significantly (p < 0.05) increased the hardness, chewiness, buriedness degree of tryptophan and gel strength, decreased the content of α-helix structure in the gels, while less change occurred in gel whiteness and network structure. Basil significantly (p < 0.05) reduced the buriedness degree of tryptophan, gel strength and whiteness, and deteriorated the gel structure. Nevertheless, the addition of DIMP or basil reduced the bitterness induced by KCl and improved the overall acceptability scores of gels of the N group. Moreover, there was no distinct difference in moisture content and water-holding capacity between all groups. Therefore, replacing sodium chloride in UFMG with 25% potassium chloride and 5% DIMP may be an ideal sodium salt substitution strategy.